Analisis Dampak Kebijakan Pendidikan Terbaru Pada Manajemen Sekolah - Iqlimatun Hasanah; Laily Salsabillah; Zaid Alaudin; Hesti Kusumaningrum (Universitas Maritim AMNI Semarang, 2024)
This article conducts an in-depth analysis of the impact of the latest educational virtues on school management. The growing educational virtues, such as the focus on technology-based learning, the development of more flexible curricula, and increased parental involvement, have brought about significant changes in the way schools are organized and led. The analysis highlights how these virtues affect school operational efficiency, educational quality, and student motivation. In addition, the article discusses the challenges faced by school management in implementing these educational virtues, as well as effective strategies to overcome them. Thus, this article provides comprehensive insights into how the latest educational virtues can improve school management performance and achieve better educational goals.